Factors Related To The Provision Of Complete Basic Immunization To Ballta In Puskesmas Sukajadi District The Year 2022 - Prihatining Peni; Rizki Amalia; Eka Rahmawati; Suprida (Institute of Computer Science (IOCS), 2022)
Based on data obtained from The Global Alliance for Vaccines and Immunization (GAVI), the World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) it is stated that at least 80 million children aged less than 1 year are at risk for suffering from Diphtheria, Measles. and Polio due to disruption of routine immunization services in the midst of the Covid-19 pandemic. This study aims to determine the relationship between knowledge, attitudes and husband's support simultaneously with the completeness of basic immunization for infants at the Sukajadi Health Center, Banyuasin Regency in 2022. The method in this study used a cross sectional with a population of 45 respondents and a sample of 45 respondents using accidental sampling technique. Data analysis used chi square statistical test with p value value (0.05). The results of this study were from 15 respondents who had good knowledge, 11 people (73.3%) gave complete basic immunization with p value = 0.02, from 23 respondents who had a positive attitude as many as 15 people (65.2%) who gave basic immunization complete p value = 0.02, meanwhile, from 21 respondents who received husband's support as many as 16 people (76.2%) p value = 0.001. From this study, we can conclude that there is a simultaneous relationship between knowledge, attitude and husband's support for the completeness of basic immunization for children under five at the Sukajadi Public Health Center, Banyuasin Regency in 2022